Performance and preference of broilers provided dual light warmth - D.J. Aldridge; C.G. Scanes; M.T. Kidd (Journal of Applied Poultry Research, 2021)
SUMMARY: The present studies evaluated the use of 2 common poultry specific Light Emitting Diodes (LEDs) of differing light warmth (2,700 K and 5,000 K). Additionally, the studies evaluated the effects of providing a choice between LED bulbs of differing light warmth to broilers for production, distribution, feeding, and drinking behavior. Chicks were housed in choice systems consisting of 2 rooms with separate illumination. Systems were divided into 3 treatments: 1) Cool-cool LED at 5,000 K on both rooms; 2) warm-warm at 2,700 K on both rooms, and 3) cool-warm with one side at 5,000 K and the other at 2,700 K. Distribution and consumption behaviors were observed for the cool-warm treatment using a remote video system. Production was assessed for all treatments and 2 consecutive trials were conducted. The BW of cool-warm treatment (study 1: 2.954 kg, study 2: 3.240 kg) were greater (P ≤ 0.05) than warm-warm (study 1: 2.816 kg and study 2: 3.110 kg) while cool-cool were intermediate (2.867 kg and 3.164 kg). There was no effect of treatment on feed:gain in either trial. Birds in the cool-warm treatment exhibited a clear preferential (P ≤ 0.05) pattern for warm light during the first and last hour of the 16 h light period. No treatment differences (P ≥ 0.05) were observed for feeding and drinking. Lights of differing light warmth improved final BW of broiler chickens.